UANG SEBAGAI SIMBOL KEKUASAAN : ANALISIS PIERRE BOURDIUE - Safitri, Indy; Agung Permadi; Meilani Rizka Mutiarani; Vieronica Varbi Sununianti; Istiqomah; Deni Aries Kurniawan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Money in modern society does not merely function as a medium of economic exchange, but has also transformed into a symbol of power and a tool of social domination. This study aims to map the development of research on money as a symbol of power through Pierre Bourdieu’s perspective within the 2018–2025 period. The method used is a literature review to identify trends, main themes, methods, and research gaps from 16 related scientific articles. The results of the analysis indicate that the focus of research has evolved from basic concepts such as habitus and capital toward more complex issues, including money politics in democracy, the cultural meaning of uang panai, and symbolic capital in the digital era. Another finding reveals that qualitative approaches still dominate this field of study, although there are limitations in terms of empirical field data support. This study is expected to provide a theoretical foundation for developing practical solutions in understanding the management of symbolic power in society.